An investigation of the role of ASPP2 in HIF signaling and cancer - Chan, HF (2020)
The ability to sense and respond to hypoxia is essential for the survival of living organisms and is frequently co-opted by tumor cells to adapt to hypoxic microenvironment. As the pivotal transcription factor for hypoxic responses, the hypoxia inducible factors (HIFs) transactivate a wide repertoire of genes that can mediate divergent functional outcomes. The regulation of HIF target gene selectivity is complex, involving the canonical regulation by oxygen sensors prolyl hydroxylases and factor inhibiting HIF (FIH) and the regulated recruitment of transcriptional cofactors, such as p300. However, how HIF target gene selectivity is regulated in cancers has yet to be fully understood.